Evaluating the Impact of Interdisciplinary Learning Factory Models on Innovation Skills Using Statistical Analysis - Moyo, Kgomotso; Sucihatiningsih Dian Wisika Prajanti; Muhtarom, Muhtarom; Faudzul Adzim (Pandawan Sejahtera Indonesia, 2026)
This study examines the impact of interdisciplinary learning factory models on the development of students innovation skills in higher education environments that integrate academic learning with industrial practices. The increasing demand for graduates with strong innovative competencies highlights the need for interdisciplinary learning approaches that effectively bridge theoretical knowledge and real-world industrial applications within learning factory settings. The main objective of this research is to evaluate the influence of interdisciplinary learning factory models on key dimensions of innovation skills, including creative thinking, problem-solving, collaboration, and critical thinking abilities. A quantitative research design was employed using structured survey instruments administered to students participating in interdisciplinary learning factory programs, and the data were analyzed through statistical techniques, including descriptive analysis, reliability and validity testing, and inferential statistical methods to examine the relationships between variables. The findings indicate a significant and positive effect of interdisciplinary learning factory models on students innovation skills, demonstrating that integrated and collaborative learning environments effectively foster innovative competencies and enhance learning outcomes. These results suggest that interdisciplinary learning factory models represent a powerful educational strategy for strengthening innovation-oriented skills in higher education, offering theoretical contributions to learning factory research and practical implications for educational institutions in designing interdisciplinary learning frameworks that support sustainable innovation and alignment with industry needs.